Novel synthesizing method of pH-dependent doxorubicin-loaded anti-CD22-labelled drug delivery nanosystem - Sun M; Wang J; Lu Q; Xia G; Zhang Y; Song L; Fang Y (Dove Medical Press, 2015)
Mengjiao Sun,1,* Jun Wang,1,* Qin Lu,1 Guohua Xia,2 Yu Zhang,3 Lina Song,3 Yongjun Fang11Department of Hematology/Oncology, Nanjing Children’s Hospital, Nanjing Medical University, 2Department of Hematology, Zhongda Hospital, Medical School, Southeast University, 3State Key Laboratory of Bioelectronics, Southeast University, Nanjing, People’s Republic of China*These authors have contributed equally to this workAbstract: The objective of this study was to investigate the anticancer efficacy of dimercaptosuccinic acid-modified iron oxide magnetic nanoparticles coloaded with anti-CD22 antibodies and doxorubicin (anti-CD22-MNPs-DOX) on non-Hodgkin’s lymphoma cells. The physical properties of anti-CD22-MNPs-DOX were studied and its antitumor effect on Raji cells in vitro was evaluated using the Cell Counting Kit-8 assay. Furthermore, cell apoptosis and intracellular accumulation of doxorubicin were determined by flow cytometry. The results revealed that anti-CD22-MNPs-DOX inhibited the proliferation of Raji cells, significantly increased the uptake of doxorubicin, and induced apoptosis. Therefore, it was concluded that a coloaded antibody and chemotherapeutic drug with magnetic nanoparticles might be an efficient targeted treatment strategy for non-Hodgkin’s lymphoma.Keywords: doxorubicin, anti-CD22 antibody, drug delivery system, target selection, non-Hodgkin lymphoma